Social Lens: Personalization Around User Defined Collections for Filtering Enterprise Message Streams - Daly, Elizabeth; Muller, Michael; Gou, Liang; Millen, David (Proceedings of the International AAAI Conference on Web and Social Media, 2021)
Social media has led to a data explosion and has begun to play an ever increasing role as a valuable source of information and a mechanism for information discovery. The wealth of data highlights the need for methods to filter and sort information in order to allow users to discover useful information. Most traditional solutions focus on the user, either the user’s social network, or a form of personalization based on collaborative filtering or predictive user modeling. This paper presents a novel algorithm to view information through a lens based on a user defined collection while excluding the attributes of the user from the analysis. As a result, the lens is transparent, tunable and sharable amongst users and, additionally allows both a reduction in information overload while discovering new related content.